Brand loyalty as mediator of brand image-repurchase intention relationship of premium-priced, high-tech product in Indonesia - Hetty Karunia Tunjungsari; Jhanghiz Syahrivar; Chairy Chairy (Universitas Kristen Maranatha, 2020)
This research aims to examine whether there is a mediating role of brand loyalty in the relationship between brand image and repurchase intention of premium-priced, high-tech product in Indonesia. We chose Apple brand in this research through a preliminary study involving 50 respondents. From the self-administered survey, we concluded Apple were perceived as the premium-priced, high-tech product. After the preliminary study, we collected 210 users of Apple products to participate in our research. Hypotheses testing were done using linear regression in IBM SPSS Statistics version 24 and Hayes’ Macro Process version 3.3 model 4. Research findings show that all hypotheses were supported by the data, brand image significantly and positively influences repurchase intention and brand loyalty mediates the influence of brand image on repurchase intention. Research implications are discussed further in this article.